2017
DOI: 10.1038/s41598-017-08370-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tumour related genes by dynamic epigenetic alteration at enhancer regions in gastric epithelial cells infected by Epstein-Barr virus

Abstract: Epstein-Barr virus (EBV) infection is associated with tumours such as Burkitt lymphoma, nasopharyngeal carcinoma, and gastric cancer. We previously showed that EBV(+) gastric cancer presents an extremely high-methylation epigenotype and this aberrant DNA methylation causes silencing of multiple tumour suppressor genes. However, the mechanisms that drive EBV infection-mediated tumorigenesis, including other epigenomic alteration, remain unclear. We analysed epigenetic alterations induced by EBV infection especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 62 publications
1
43
0
Order By: Relevance
“…Moreover, not only DNA methylation but also other epigenetic alterations caused by EBV infection may contribute to carcinogenesis. EBV infection causes enhancer activation and repression, which may be associated with gastric carcinogenesis [31]. A recent study suggested that enhancer activation through ATF3 might be involved in carcinogenesis [32].…”
Section: Epigenetic Aberrant In Gastric Cancermentioning
confidence: 99%
“…Moreover, not only DNA methylation but also other epigenetic alterations caused by EBV infection may contribute to carcinogenesis. EBV infection causes enhancer activation and repression, which may be associated with gastric carcinogenesis [31]. A recent study suggested that enhancer activation through ATF3 might be involved in carcinogenesis [32].…”
Section: Epigenetic Aberrant In Gastric Cancermentioning
confidence: 99%
“…ChIP-seq analysis was performed as described [20] . ChIP libraries were constructed using NEBNext ChIP-seq Library Prep Reagent Set for Illumina (NEB, Ipswich, MA), quantified using Bioanalyzer (Agilent, Santa Clara, CA), and sequenced at concentration of 4 pM on Illumina Hiseq (Illumina).…”
Section: Methodsmentioning
confidence: 99%
“…One outstanding question from these studies is whether clearly distinct GC subsets are characterized by unique regulatory element landscapes. In this regard, Okabe and colleagues demonstrated pro‐oncogenic enhancer dysregulation through redistribution of repressive histone marks following EBV infection in vitro, thereby establishing a potential EBV‐induced enhancer landscape unique to this subtype …”
Section: Multifaceted Molecular Classification Of Gcmentioning
confidence: 99%